'"It's relentless": The impact of working with primarily high-risk offenders': A practitioner response. (March 2017) - Lee, Rosie
This piece is a response to Phillips, Westaby and Fowler's article '"It's Relentless": The Impact of Working with Primarily High-Risk Offenders'. Their research considers the pressure felt by practitioners supervising a predominantly 'high-risk' caseload due to increased public protection responsibilities and organizational failure to provide guidance as to prioritization of risk and need. This response further explores the emotional impact of supervising a high-risk caseload. This is discussed in reference to the case manager's ability to engage with a client's personal experiences of trauma within an organizational culture, which prioritizes public protection and concern for the potential for something to 'go wrong'. It is argued supervisory support is inadequate and additional resources should be focused on practitioners' need to reflect on the emotional impact of working with a high-risk caseload.